Association between socio-demographic factors and smoking status of dual and single tobacco users among Malaysian university students - Elsaieh, Afaf Masaud; Shohaimi, Shamarina; Mohd Nadzir, Mohd Noor Hisham; Mohd Puad, Mohd Hazwan; Ab Rahman, Abdul Hafiz; Masoud Elsaihi, Fatma (South Florida Publishing, 2023)
Objective: In order to develop effective interventions and policies to address the growing trend of dual tobacco and e-cigarette use among Malaysia's younger generation, it is crucial to understand the socio-demographic factors that influence this behaviour. This study aimed to bridge this knowledge gap by examining the relationship between socio-demographic characteristics and smoking status among university students in the Klang Valley region of Malaysia. Method: The researchers used a cross-sectional field survey approach to collect data through a questionnaire administered to 386 university students in the Klang Valley region of Malaysia. The selected universities included Universiti Putra Malaysia (UPM), Universiti Kebangsaan Malaysia (UKM), Universiti Malaya (UM), and Sunway University, providing a diverse representation of the country's young population. Results: The findings highlight the complex nature of factors influencing smoking behaviours, revealing that socio-demographic variables have a limited impact on an individual's smoking status. However, gender emerged as a notable exception, strongly associated with smoking status. This suggests that gender dynamics may play a significant role in shaping tobacco and e-cigarette use among students. Furthermore, the study identified additional influences, such as peer pressure, accessibility of tobacco products, and perceptions towards smoking, which are likely to affect smoking behaviours. Although these aspects were not the primary focus of the study, their importance is evident. Conclusions: The study provides valuable information that can help policymakers, health professionals, and educators develop effective strategies to reduce smoking among young Malaysians. However, it also highlights the need for further research to better understand the complex factors involved in smoking and to develop more effective interventions to reduce smoking among university students. Research Implications: The study's findings can guide the development of targeted interventions, educational campaigns, and policies aimed at reducing tobacco and e-cigarette use among university students. The strong association between gender and smoking status may also guide tailored interventions for different gender groups. Originality/value: The originality of this study lies in its focused investigation of socio-demographic factors influencing dual tobacco and e-cigarette use among university students in Malaysia. The research not only reveals the limited influence of socio-demographic variables but also highlights the significance of gender and other unexplored factors, providing a nuanced understanding of smoking behaviours within this specific context.